Safety Culture in the Operating Room: Variability Among Perioperative Healthcare Workers. Issue 6 (1st September 2021) - Pimentel, Marc Philip T.; Choi, Stephanie; Fiumara, Karen; Kachalia, Allen; Urman, Richard D.
Abstract : Introduction: Safety culture is defined as the product of individual and group values, attitudes, perceptions, competencies, and patterns of behavior that determine an organization's health and safety management. There is a lack of studies assessing patient safety culture in the perioperative setting. Objectives: We examined safety culture at a single tertiary care hospital, across all types of surgery, using previously collected data from a validated survey tool. We aim to understand how safety culture varies among perioperative staff. Methods: The Hospital Survey on Patient Safety Culture was administered at a single tertiary care hospital in 2014. We identified 431 respondents as perioperative healthcare workers: surgery attending physician, surgery trainee physician, anesthesia attending physician, anesthesia trainee physician, nurse, and technician. We calculated percent positive scores for each dimension of safety culture, as well as a composite score. Pairwise comparisons were calculated via analysis of variance. Results: The average response rate was 67%. The dimensions with the highest average percent positive scores were teamwork within hospital units (69%) and organizational learning and continuous improvement (57%). The dimensions with the lowest scores were feedback and communication about error (34%) and hospital handoffs and transitions (30%). Surgery attending physicians perceived the strongest safety climate overall, whereas nurses and surgical technicians perceived significantly worse safety climate. Conclusions: We observed significant variability in perioperative safety culture, across dimensions of safety climate, professional roles, and levels of training. These variations in safety culture should be addressed when implementing culture change programs in the perioperative setting.